PKM penulisan karya ilmiah mahasiswa Fakultas Ilmu Keolahragaan Universitas Negeri Makassar - Hasmyati Hasmyati; Sarifin Sarifin; Ricardo Valentino L (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Scientific work as an important element in the lecture process is sometimes still considered a scourge by some students. This happens because of the many important elements that students must pay attention to. The scientific work in question is in the form of a thesis, thesis, research report, and so on. Certain types of scientific works must be made by students who are undergoing lectures. The problem among students is the method of writing scientific papers, sometimes students do not follow the standard rules according to existing theories. They should have mastered the rules wrapped in research methodology. The method used in this activity was lecture and question and answer and practice carried out for three days. This activity is very useful for students to know the signs that must be known when conducting research, students will find it easier when the final thesis making process. The participants realized that this activity was able to provide additional knowledge about making scientific papers. Suggestions given with this activity are expected to the local bureaucracy especially FIK UNM and all study programs within FIK UNM to send representatives in each training activity of writing scientific papers and involve students in competitions of writing scientific papers.